The Relantionship Between Gestational Age, Parity, and Compliance with Fe Tablet Consumption with Anaemia in Pregnant Women at Seteluk Health Center in 2024 - Andani, Azalia Asri; Wanadiatri, Halia; Karmila, Dany; Sudiarta, I Gede (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Anaemia in pregnant women is one of the health problems that can adversely affect the mother and fetus. Factors such as gestational age, parity, and Fe tablet consumption compliance are thought to have an association with the incidence of anaemia in pregnant women. The study aims to determine the relationship between gestational age, parity, and compliance with Fe tablet consumption with the incidence of anemia in pregnant women at the Seteluk Health Center. The research method uses observational analytics with a cross-sectional design. The sampling technique uses purposive sampling. The research sample is 76 samples according to the inclusion and exclusion criteria. Data collection is done through questionnaires and medical records. Data analysis is done using the chi-square statistical test. The results showed that 52.6% of respondents had risky gestational age (≥13-40 weeks) and 47.4% were not at risk (<13 weeks). Risky parity (>2 times) was found in 10.5% of respondents, while 89.5% had non-risky parity (≤2 times). Adherence to Fe tablet consumption was 56.6%, while 43.4% were non-compliant. The results of the chi-square statistical test showed a p value for the association of gestational age with anaemia incidence of 0.004, parity of 0.666, and adherence to Fe tablet consumption of 0.023. Conclusion: Gestational age and Fe consumption compliance were associated with anaemia incidence in Seteluk Health Centre. However, parity is not associated with anaemia among pregnant women in Seteluk Health Centre.